THE INFLUENCE OF THE FLIPPED CLASSROOM MODEL ON TABLE TENNIS LEARNING OUTCOMES - Dartini, Ni Putu Dwi Sucita; Adi, I Putu Panca; Spyanawati, Ni Luh Putu (Jurnal Edukasi Citra Olahraga, 2025)
. Flipped classroom is a strategy in the blended learning model that combines direct or face-to-face learning (synchronous) offline with indirect or independent learning (asynchronous) online. Flipped classroom is a learning model where students study the material independently through e-learning before class and then meet in class offline to discuss the material that has been studied. The purpose of this study was to determine the effect of the flipped classroom learning model on table tennis learning achievement. This research method is an experiment with a pre-test post-test control group design. The population in the study were fourth semester students of the Physical Education, Health and Recreation Study Program who programmed the course table tennis learning, while the research sample was randomized using the cluster random sampling technique. The data collection method used multiple choice written tests and performance tests. The results showed that there was a significant difference between the use of flipped classroom and conventional models (with sig 0.04 <0.05). The flipped classroom model provides better results in increasing the average learning outcomes of table tennis.